ANALYSIS OF FACTORS AFFECTING PROFIT MANAGEMENT IN PROPERTY COMPANIES - Desi Renofa Simanjuntak; Yois Nelsari Malau; Yuni Kencana Wari (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study aims to determine the effect of Financei Leverage, Return on Assets, Net Profit Margin, Company Size on Management in Property Companies listed on Bursa Efek Indonesia 2017-2019. The data used is sourced from annual data via the www.idx.co.id website, which has been selected based on predetermined criteria. The population used in this company is all property companies, totaling 15 companies, using a purposive sample of 45 samples. This research is expected to become a science that can help further researchers and can also help students or the general public who need information from this research. From this research, it can be seen that Finance Leverage and partially old management have no influence on Return.On in Property Companies, while Net Profit Margin and Company Size partially affect Profit Management in Property Companies